Climate negotiations in times of multiple crises: Credibility and trust in international climate politics after COP 27 - Marian Feist; Oliver Geden (Stiftung Wissenschaft und Politik (SWP), 2023)
The 27th Conference of the Parties (COP 27) to the United Nations Framework Convention on Climate Change (UNFCCC) in Sharm el-Sheikh, Egypt, was marked by multiple crises and the shaken confidence of developing countries in the multilateral process. Nonetheless, an agreement was reached on the critical issue of loss and damage, even though many key aspects still need to be fleshed out. With regard to emission reductions, there is a credibility crisis that threatens to worsen, not only because political priorities have shifted following Russia's attack on Ukraine. In order to strengthen international climate cooperation in the coming years, it will be crucial to honour existing commitments, adhere to agreed processes, and show diplomatic tact in dealing with partner countries.
Keywords: 320; Klimapolitik; Klimawandel; UN-Klimarahmenkonvention (UNFCCC); 27. Vertragsstaatenkonferenz (COP 27) in Scharm El-Scheich; Schäden und Verluste; Loss and Damage; Klimaschutz; Mitigation; Klimafolgenanpassung; Adaptation; Global Shield; climate policy; climate change; United Nations Framework Conven tion on Climate Change; UNFCCC; COP 27; Sharm el-Sheik; loss and damage; mitigation; climate change adaptation; Global Shield; Vulnerable 20; Nationally Determined Contributions; NDCs; Green Climate Fund; GCF